Analysis of Land Cover Change of Lake Rawapening with Sentinel 1 - Synthetic Aperture Radar Data - Jaelani, Lalu Muhamad; Putri, Rizky Annisa (Institut Teknologi Sepuluh Nopember, 2017)
― Approximately 90% of freshwater on the earth surface is stored by lakes and reservoirs that provide benefits for human life such as for daily water needed, industry, agriculture, transportation, hydroelectric power and tourism. Most watersheds (DAS) and lakes in Indonesia have experienced the quality and quantity degradation caused by population growth, land conversion and erosion. Lake Rawapening in Central Java is one of fifteen Indonesian National Priority Lakes that should be seriously monitored and well managed. For routine monitoring of land cover change of the lake and its watershed, an optical remote sensing data that generally used was facing a problem related to cloud cover over the area of lake. In this research, we propose the utilization of Sentinel 1A, an active RADAR remote sensing data which can penetrate the cloud, thus more effective for observing land cover changes. The classification result of December 2016 data has strong relationship with field object (Kappa= 94.218%). All water objects were recognized as water, 94.595% of wetland were recognized as wetland (others as water), 91.379% of vegetation were recognized as vegetation (others as agriculture), 95.238% of agriculture were recognized as agriculture (others as urban) and 96.774% of urban were recognized as urban (others as wetland and agriculture). During May and December 2016, the landcover change was triggered by high precipitation in December and rapid-uncontrolled growth of water hyacinth in May. During May and December 2016, the landcover change was triggered by high precipitation in December and rapid-uncontrolled growth of water hyacinth in May.